2015
DOI: 10.1186/s40064-015-1218-x
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Cushing syndrome and adrenal insufficiency during concomitant therapy with ritonavir and fluticasone

Abstract: Ritonavir is a potent inhibitor of the cytochrome P450 enzyme CYP3A4 and is subject to multiple drug–drug interactions. This becomes especially important when the patient is also taking medications metabolized through CYP3A pathway as increased and potentially toxic drug levels may ensue. Herein we present one such interaction wherein a 57 year old gentleman with human immunodeficiency virus (HIV) infection on highly active antiretroviral therapy that included ritonavir, had addition of fluticasone inhaler to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 49 publications
(24 reference statements)
0
28
0
6
Order By: Relevance
“…An early morning serum cortisol level <80 nmol/L strongly suggests adrenal insufficiency [22]. antagonists or long acting anticholinergic agent such as tiotropium [21]. In our case, we had no other alternative to ritonavir and the exogenous steroid was not a prescription drug.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…An early morning serum cortisol level <80 nmol/L strongly suggests adrenal insufficiency [22]. antagonists or long acting anticholinergic agent such as tiotropium [21]. In our case, we had no other alternative to ritonavir and the exogenous steroid was not a prescription drug.…”
Section: Discussionmentioning
confidence: 67%
“…These test include: failure to suppress serum cortisol with low doses of oral dexamethasone; loss of the normal circadian rhythm of cortisol, with inappropriately elevated late-night serum or salivary cortisol and increased 24-hour urine free cortisol [20]. In the case of Iatrogenic Cushing's syndrome with secondary pituitary-adrenal axis suppression, the exogenous steroid suppresses Pituitary production of corticotropin (ACTH), leading to atrophy of the adrenal cortex and adrenal insufficiency [21]. As a result, the diagnosis is confirmed by low early morning serum cortisol levels and subnormal response to standard ACTH stimulation test.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, CS in our patient developed following shorter term (1 month) use of low‐effective steroid fluorometholone compared to other reported cases. The effects of steroids can be potentiated when they are used with a cytochrome p450 inhibitor, which in turn lead to Cushing syndrome . However, the only drug that our patient used in addition to fluorometholone, netilmicin, is not known to have any effects on the hepatic microsomal p450 system.…”
Section: Discussionmentioning
confidence: 87%
“…[7][8][9][10][11][12][13][14] In a recent literature review, Epperla et al reported a total of 37 cases of iatrogenic Cushing's syndrome and adrenal suppression as a result of concomitant use of fluticasone and ritonavir in which the time between co-administration and the development of symptoms ranged from two weeks to two years. 7 Another review showed that it took between two weeks and 12 months for patients to experience a complete resolution of symptoms after either drug was discontinued. 8 In the current case, the patient had low ACTH and morning cortisol levels and a subnormal response to synthetic ACTH.…”
Section: Discussionmentioning
confidence: 99%